Gambaran hasil hemoglobin pada anak yang menghirup Lem kaleng (fox) di daerah jalan abdul kadir kota makassar - Ardiansyah Ardi; Dian Rahmawati Djali (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2020)
Fox glue is a sticky substance that holds 2 or more things together. Many users of fox glue are still not aware of the dangers of inhaling fox glue that can be harmful to health. The content of LSD (Lysergic Acid Diethylamide) which when inserted into the human body can change a person's mood, feelings, thoughts, behavior and can also attack organs such as the brain, heart and lungs. This study aims to determine the description of hemoglobin results in children who inhale canned glue (FOX) in the area of Jalan Abdul Kadir, Makassar City. The results of the hemoglobin examination were obtained using the MINDRAY BC3600 tool. Based on The conclusion of the five blood samples taken by purposive sampling technique, all of the hemoglobin results showed normal results, namely sample A, 16.8 gr/dl, sample B, 14.0 gr/dl, sample C, 14.4 gr/dl, sample D, 13 ,8 gr/dl, and sample E, 15.2 gr/dl. Thus, it can be concluded that children who inhaled the glue can of fox experienced normal hemoglobin results. Based on the results of the research above, it is recommended that children who inhale fox glue should pay more attention to their own health by stopping the use of fox glue